Religious Leaders as Peacebuilders: Assessing the Role of Christian and Muslim Clergy in Conflict Prevention in Southwest Nigeria. - Oyebanji, Israel Temitope; Oyunwola, Taiwo Olayinka (MAHABBAH: Journal of Religion and Education, 2024)
Despite numerous Christian-Muslim dialogue initiatives in Southwest Nigeria, religious conflicts persist, leading to loss of lives, property destruction, and displacement of people. This is the aim of the study, which examined the effectiveness of Christian-Muslim dialogue in promoting peace-building in Southwest Nigeria. The study uses a qualitative approach, involving a review of relevant literature on the impact of interfaith dialogue initiatives on building trust, resolving conflicts, and fostering peaceful coexistence among Christians and Muslims in Nigeria. The study's findings indicated that Christian-Muslim dialogue has significantly contributed to reducing tensions and improving relationships between the two religious groups. Initiatives to promote dialogue have made it easier to comprehend, empathise with, and work together, which has decreased violence and enhanced conflict resolution techniques. However, challenges persist, including prejudices, political manipulation, and limited institutional support. The present study highlighted the need for sustained and inclusive dialogue efforts, involving religious leaders, policymakers, and grassroots communities, to consolidate gains and promote sustainable peace in Nigeria. The study's findings have implications for peace-building initiatives in other conflict-affected countries like Nigeria, with religious diversity.